Aspek Hukum Dalam Perlindungan Konsumen Pada Kegiatan Bisnis Digital Di Indonesia - Putri, Bela Karmelia; Khoirunisa, Vio; Nuarsaputri, Amanda; Natasya, Natasya (Universitas Batanghari Jambi, 2026)
The development of digital technology has significantly driven the growth of digital businesses in Indonesia and created changes in people's economic transaction patterns. While this situation provides convenience and efficiency, it also raises various legal issues related to consumer protection, particularly in electronic transactions conducted without direct interaction between the parties. This study aims to analyze the legal aspects of consumer protection in digital business activities and assess the effectiveness of applicable regulations in providing legal certainty and justice. The research method used is a qualitative method with a normative juridical approach through literature review. The results show that consumer protection has been regulated quite comprehensively, but its implementation still faces obstacles such as low legal literacy, weak supervision, and unequal bargaining power of consumers. Therefore, strengthening regulations and legal education are strategic steps.